The role of the industrial psychologist in managing the psychological impact of COVID-19 in the workplace - Moralo, Thapelo Sendry; Graupner, Lené Ilyna (Frontiers in Psychology, 2022)
Recently, the world experienced dramatic changes due to the onset of the COVID-19 pandemic. Working remotely led to employees feeling isolated and experiencing fatigue and depression. The responsibility of addressing the psychological wellbeing of employees lies with industrial psychology practitioners. They support line management by counselling employees experiencing social and psychological problems. The objective of the present study was to explore the role of the industrial psychology practitioner in managing the psychological impact of COVID-19 on employees. Using a homogeneous sampling technique, a qualitative research design was employed based on social constructivism. Semi-structured interviews and a qualitative survey were utilised to gather the data from industrial psychology practitioners (n =22) registered as psychologists and interns. Thematic analysis was employed to analyse the data. Most participants believed that the onset of COVID-19 led to accelerated change in the workplace. The findings suggest that an industrial psychology practitioner’s role in the changing world of work enables organisations to be prepared for the changes by providing multi-level interventions. Recommendations are made to organisations to implement interventions to facilitate support for employees in their attempt to deal with the psychological impact of COVID-19 on employees.